2019
DOI: 10.2174/1389201020666190506124548
|View full text |Cite
|
Sign up to set email alerts
|

Does Nimodipine, a Selective Calcium Channel Blocker, Impair Chondrocyte Proliferation or Damage Extracellular Matrix Structures?

Abstract: Background: The study aimed to investigate the effects of the active ingredient, nimodipine, on chondrocyte proliferation and extracellular matrix (ECM) structures in cartilage tissue cells. Methods: Chondrocyte cultures were prepared from tissues resected via surgical operations. Nimodipine was then applied to these cultures and molecular analysis was performed. The data obtained were statistically calculated. Results: Both, the results of the (3-(4,5 dimethylthiazol2-yl)-2,5-diphenyltetrazolium (MTT) ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Kaplan and colleagues demonstrated that Nimodipine impaired chondrocyte proliferation and damaged extracellular matrix structures in vitro. 31 Second, the vasodilating effects of CCBs might be impaired by NSAIDs. Pavlicević and colleagues found that NSAIDs did not significantly change body weight, urinary output, serum creatinine, or serum/urinary electrolyte profile, and they concluded that NSAID's pro‐hypertensive effects seem mainly due to vasoconstriction rather than volume expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan and colleagues demonstrated that Nimodipine impaired chondrocyte proliferation and damaged extracellular matrix structures in vitro. 31 Second, the vasodilating effects of CCBs might be impaired by NSAIDs. Pavlicević and colleagues found that NSAIDs did not significantly change body weight, urinary output, serum creatinine, or serum/urinary electrolyte profile, and they concluded that NSAID's pro‐hypertensive effects seem mainly due to vasoconstriction rather than volume expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin alpha-IIb/beta-3 (ITGA2B:ITGB3) acts as a receptor for multiple proteins, such as fibronectin, prothrombin, and thrombospondin. It is involved in chondrocyte growth and proliferation [ 45 ]. Signal transducer and activator of transcription 3 (STAT3) protein changes the expression level of various genes to adapt to cell stimuli from many cytokines and growth factors, including HGF, EGF, BMP2 and IL5 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results obtained from assays using animal tissues may diverge from those using human tissues, which may result in misleading outcomes (6)(7)(8)(9)(10)(11)13,14). Commercial cell lines are known to comprise only a single type of cell, and there are no complicated coordination mechanisms in the microenvironment of the cells (6)(7)(8)(9)(10)(11)13,14). They do not have the same genotypic and/or phenotypic characteristics as in the human body; therefore, the results of studies using cell lines may also be misleading (6)(7)(8)(9)(10)(11)13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Microphotographs of cell structures were obtained ( Fig. 1; second lane), and the images were evaluated using the CytoVision ® v 7.0 (DM6000B; Leica Microsystems GmbH) capture station imaging program (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Preparation Of the Primary Cell Cultures And Application Of mentioning
confidence: 99%
See 1 more Smart Citation